CONTRIBUTION TO THE STUDYES OF THE KRAJIŠTA OF THE MEDIEVAL SERBIA – KRAJIŠTA OF PETRUS AND LIPOVAC (Heritage, 2024)
Krajošta, or krajine, were documented in historical sources and already were explore in Serbian historiography. Those teritories were situated on border of the Serbian medieval state, with main purpose to protect the innerland of the kingdom. They were formed around one, main fort. Recent reaserch of the  krajinas around forts in Petrus (Petruško krajište) and Lipovac (lipovačko krajitšte), shows that those teritories and their main routes were controled by sistem of the fortificatons that allowed surveillance ovet their teritory, and protection over the main roads.
Keywords: krajište, Petrus, Lipovac, Middle Ages, fortress